202k views
1 vote
Solve the system of equations - 6x + 5y = 0 and -5x + 5y = -5 by combining

the equations.
|(-6x +5y = 0)
- 5х +5y
-5)
- 6x +5y
0
-5x +5y = -5
0 X+y=
try

User Doctorram
by
4.1k points

1 Answer

4 votes

9514 1404 393

Answer:

(x, y) = (-5, -6)

Explanation:

The coefficients of y are the same, so we can eliminate y by subtracting one equation from the other. Here, we choose to subtract the first from the second, so that the coefficient of x ends up positive.

(-5x +5y) -(-6x +5y) = (-5) -(0)

x = -5 . . . . . . simplify

-6(-5) +5y = 0 . . . . . . substitute x into the first equation

6 +y = 0 . . . . . . . . . . divide by 5

y = -6 . . . . . . subtract 6

The solution to the system of equations is (x, y) = (-5, -6).